Nanoscale engineering in agricultural management - Raliya, Ramesh (CRC Press, Taylor & Francis Group, 2019)
Agriculture plays a vital role in our lives, providing food and economic benefits. Today, it faces severe challenges, due to decreasing arable land, depleting natural resources, changing climate pattern, and yet increasing demand for food. The recent introduction of nanotechnology in agriculture offers sustainable and precise solutions for developing smart agriculture practices and addressing the challenges faced by the ag-sector. Therefore, it is essential to understand this new science from a multidimensional perspective. Experts in the field have contributed in putting together this volume, covering topics like plant growth, protection and management using engineering nanoscale materials. The chapters in the book have been peer-reviewed and selected for publication based on independent reviewers' reports. The book covers very specific, in-depth, and fundamental and applied aspects of the latest ag-nanotechnology research. It is hoped that each chapter of the book will be very useful for researchers, policy makers, and other audiences from interdisciplinary scientific subjects